2021
DOI: 10.3390/polym13162633
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Biodegradation Pattern of Collagen Matrices for Soft Tissue Augmentation

Abstract: Collagen matrices have become a great alternative to the use of connective tissue grafts for soft tissue augmentation procedures. One of the main problems with these matrices is their volume instability and rapid degradation. This study has been designed with the objective of examining the degradation of three matrices over time. For this purpose, pieces of 10 × 10 mm2 of Fibro-Gide, Mucograft and Mucoderm were submitted to three different degradation tests—(1) hydrolytic degradation in phosphate buffer soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…Evolution X-fine was the only membrane that reached 50 d of immersion, but with a great rate of resorption in C. histolyticum (Tables 2 and 3). The rapid degradation of collagen membranes in this medium has been previously verified by other authors, Vallecillo et al [34] observed early degradation when three collagen matrices were submitted to the C. histolyticum assay. Fibro-Gide, a cross-linked collagen matrix, was uniquely able to withstand 7 d of storage in a bacterial collagenase test.…”
Section: Discussionsupporting
confidence: 77%
“…Evolution X-fine was the only membrane that reached 50 d of immersion, but with a great rate of resorption in C. histolyticum (Tables 2 and 3). The rapid degradation of collagen membranes in this medium has been previously verified by other authors, Vallecillo et al [34] observed early degradation when three collagen matrices were submitted to the C. histolyticum assay. Fibro-Gide, a cross-linked collagen matrix, was uniquely able to withstand 7 d of storage in a bacterial collagenase test.…”
Section: Discussionsupporting
confidence: 77%
“…PADMs proved to possess these requirements and have previously been proposed to enhance peri-implant soft tissue regeneration, gaining attached mucosa around dental implants in the oral cavity. Several studies [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] demonstrated that due to biocompatibility as well as a sufficient physical, chemical, and mechanical stability, PADMs are replaced by new connective tissue within approximately 6–9 months, resulting in complete integration in the host tissue [ 9 , 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have investigated the biologic and chemical–physical features of PADMs [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], the biocompatibility of these matrices with human primary mesenchymal stem cells (HPMSCs) is rarely described [ 21 ]. In vitro assays of HPMSCs offer a proper model for studying the interactions of these cells with matrices.…”
Section: Introductionmentioning
confidence: 99%
“…Another important cause of a denser structure of MCS in comparison with UCS could be a partial collapse and shrinkage of the inner architecture of the collagen foam due to a hydrolytic degradation of collagen in the Tris–HCl buffer during mineralization. Surprisingly, a fast hydrolytic degradation of three different commercial porcine collagen matrices, based on native dermal type I and III collagen, was recently described by Vallecillo et al [ 50 ]. After 48 h of immersion of the samples in the phosphate-buffered saline (PBS) at 37 °C, the authors observed considerable volume and weight losses of collagen matrices—all the three matrices experienced a loss of weight between 40 and 80%.…”
Section: Discussionmentioning
confidence: 99%